2022
DOI: 10.3390/molecules27134100
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lycium ruthenicum Polyphenols on Oxidative Stress against Acrylamide Induced Liver Injury in Rats

Abstract: Acrylamide (ACR) is formed during tobacco and carbohydrate-rich food heating and is widely applied in many industries, with a range of toxic effects. The antioxidant properties of Lycium ruthenicum polyphenols (LRP) have been established before. This study aimed to research the protective effect of LRP against ACR-induced liver injury in SD rats. Rats were divided into six groups: Control, ACR (40 mg/kg/day, i.g.), LRP (50, 100, and 200 mg/kg/day, i.g.) plus ACR, and LRP groups. After 19 days, we evaluated oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Regarding the first mechanism, oxidative stress, lipid peroxides and impaired antioxidant defense in the liver are linked to the activation of cytochrome P450 (CYP) 2E1, which functions as a central pathway in the formation of high levels of ROS, being also the only enzyme involved in biotransformation of ACR in glycidamide [ 53 ]. Therefore, CYP2E1-catalyzed ACR metabolism causes an imbalance between ROS production and elimination, in the sense of excessive ROS production, then results in lipid peroxidation and increases oxidative stress, which is related to liver damage [ 53 , 73 , 74 ]. Since ACR is not only a substrate, but also an inducer of CYP2E1, with CYP2E1 overexpression being induced by ACR intoxication and associated with increased oxidant production, the prevention and treatment of ACR-induced toxicity can be supported by antioxidants that have the ability to inhibit or to downregulate CYP2E1 [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the first mechanism, oxidative stress, lipid peroxides and impaired antioxidant defense in the liver are linked to the activation of cytochrome P450 (CYP) 2E1, which functions as a central pathway in the formation of high levels of ROS, being also the only enzyme involved in biotransformation of ACR in glycidamide [ 53 ]. Therefore, CYP2E1-catalyzed ACR metabolism causes an imbalance between ROS production and elimination, in the sense of excessive ROS production, then results in lipid peroxidation and increases oxidative stress, which is related to liver damage [ 53 , 73 , 74 ]. Since ACR is not only a substrate, but also an inducer of CYP2E1, with CYP2E1 overexpression being induced by ACR intoxication and associated with increased oxidant production, the prevention and treatment of ACR-induced toxicity can be supported by antioxidants that have the ability to inhibit or to downregulate CYP2E1 [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since ACR is not only a substrate, but also an inducer of CYP2E1, with CYP2E1 overexpression being induced by ACR intoxication and associated with increased oxidant production, the prevention and treatment of ACR-induced toxicity can be supported by antioxidants that have the ability to inhibit or to downregulate CYP2E1 [ 53 ]. Regarding the second mechanism of ACR hepatotoxicity, studies have confirmed the apoptotic property of ACR in a dose- and time-dependent manner in the liver, with long-term exposure to ACR causing mitochondrial collapse and leading to apoptosis [ 53 , 73 , 74 ]. Therefore, ACR treatment alters the potential of the mitochondrial membrane of hepatocytes and may alter the expression of nuclear factor-erythroid 2-related factor 2 (Nrf2) [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant extracts with strong antioxidant activity have ameliorated organ toxicities. [17][18][19][20] Polyphenols as antioxidants display potential neuroprotective effects, mainly through reducing ROS generation and anti-apoptosis and up-regulating other endogenous antioxidant enzymes, such as superoxide dismutase (SOD), catalase, and glutathione (GSH) peroxidase both in vitro and in vivo. [21][22][23] L. ruthenicum Murr.…”
Section: Introductionmentioning
confidence: 99%